Fenomena Gerakan Hijrah di Kalangan Pemuda Muslim Sebagai Mode Sosial - Agnia Addini (Journal of Islamic Civilization, 2019)
The massive movement of the migrants to the young generation today is a new phenomenon in the Islamic movement in Indonesia. By carrying out the vision to invite the younger generation to draw closer to God Almighty, this movement is active in carrying out da'wah by using modern approaches that utilize social media as a medium of awareness. Abandoning traditionalist methods is a choice in changing the mindset of religious rituals only for middle-aged people. But Amid the popularity of Hijrah in Muslim youth with its Islamism, the behavior of 'Hijrah' itself seems to have lost its original meaning. Hijrah is only seen as a symbolic transition. Whereas Hijrah basically is not only strengthening in religious values, Hijrah has a mission of reform in every aspect of social, economic and political life.